Influence of Brand Image and Relationship Quality on Patient Satisfaction (Survey of Outpatients of Hermina Pasteur Hospital Bandung) - Ramadhan, Aji; Febrian, Feby; Mulyana, Agus (Greenation International Journal of Engineering Science, 2024)
Aji Ramadhan, 2023. The Influence of Brand Image and Relationship Quality on Patient Satisfaction (Survey on Outpatients of Hermina Pasteur Hospital Bandung), Thesis of the Winaya Mukti University Postgraduate Program, Master of Management Study Program. under the guidance of Dr. Nut Wuri Andayana, Apt., MMRS and Dr. Annisa Fitri Anggraeni, SE, MM, CISA.The development of the service industry sector, including health services, is inseparable from the demands of the community to continue to get quality health services. Various efforts have been made to improve health development that is better and more efficient and efficient, so that it can reach all levels of society. This study aims to determine and analyze the effect of brand image and relationship quality on the satisfaction of outpatients of Hermina Pasteur Bandung Hospital. The results of this study are expected to be input for Hermina Pasteur Hospital in organizing health services, especially in increasing satisfaction. The research method used is descriptive and verification analysis. The data collection used is an interview using a questionnaire accompanied by observation and literature techniques, sampling using consecutive sampling. Data collection in the field was carried out in 2023. Data analysis techniques using Path Analysis. The results showed that in general, brand image, relationship quality, and patient satisfaction tended to be quite good. There is an influence of brand image and relationship quality on patient satisfaction both simultaneously and partially at Hermina Pasteur Hospital. Hermina Pasteur Hospital must carry out service recovery for patient complaints or complaints quickly, so as not to cause dissatisfaction from patients, to handle patient complaints quickly the hospital can form a customer care program.